Second order pressure estimates for the Crank-Nicolson discretization of the incompressible Navier-Stokes Equations - Sonner, Florian; Richter, Thomas (SIAM journal on numerical analysis, 2020)
We provide optimal order pressure error estimates for the Crank-Nicolson semidis-cretization of the incompressible Navier-Stokes equations. Second order estimates for the velocity error are long known; we prove that the pressure error is of the same order if considered at interval midpoints, confirming previous numerical evidence. For simplicity we first give a proof under high regularity assumptions that include nonlocal compatibility conditions for the initial data, then use smoothing techniques for a proof under reduced assumptions based on standard local conditions only.